KUALITAS RELASIONAL (RELATIONSHIP) DALAM JASA PENJUALAN : Pengaruh Hubungan Interpersonal Wiraniaga Kartu Kredit Terhadap Loyalitas Nasabah Pada Industri Perbankan di Indonesia - Farida Jasfar (Media Riset Bisnis & Manajemen, 2004)
The Increasing function of credit card and it's role in the modem economic society, including i Indonesia. One of the most important thing in the credit card markeling is the role of salesperson in convincing the consumer for using this credit card as proporrtionally and responsible. The research about this salesperson interpersonal relationship has the objective to explore the influence of company characteristic, salesperson relationshipcharaceristic, and service quality for relationship quality and also the role of relalionship quatity as a mediating varlable. By usingthe methodological survey, this research has been succeeded in getting the sample by purposive to the 379 credit card holder. The data collection method has done by some questioner and hypothesis testing with the linear structural method which calculated with the slatistic program AMOS for Windows. The hypothesis testing about positive correlation relationship in between company charaderistic, salesperson relationship characteristic, and the service quality also supported the first hypothesis statement. In the testing of the influence of company characteristic, salesperson relationship character- islic and service quality in the relationshp quality, and also the influence of company characteristic, salesperson relationship, service quallty and the relation between relationship quality and loyalty. Salesperson rlationship characteristic also ha less and negativ influence with the relationship quality and loyally. Oly services qualliy and strong influence with the rlation quality and loyalty, like the raltionship quality has strang influence with the relation quality and loyalty, ike the relationship qualitay with the signtficance loyalty. About the role of relafionship quaity as a mediating varlable to the loyalty is as the same as the fourth hypothesis.